2000
DOI: 10.1007/pl00013663
|View full text |Cite
|
Sign up to set email alerts
|

A small-angle X-ray scattering study of the isotropic and nematic phases of V2O5 suspensions

Abstract: We report small-angle X-ray scattering experiments performed in both the isotropic and nematic phases of aqueous V2O5 suspensions. We show that the scattering in the isotropic phase can be well described in the whole accessible q-range by only considering the form factor of non-interacting ribbons. We investigate the influence of concentration and pH on the dimensions of V2O5 ribbons and show that these parameters do not have any significant effect, as long as the system stays well within the chemical stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
3
0
1
Order By: Relevance
“…It was experimentally shown that the 2D patterns of all nematic phases contain two bands due to a pseudo-lamellar ordering of at least eight lamellar distances, and a third diffuse band, related to the micellar positional ordering in the direction perpendicular to the pseudo-lamellar ordering. The existence of a structural or “correlation” peak and its position at low q values as a typical for the nematic phase arrangement was also mentioned by Holmes et al, Pelletier et al, and Davidson et al The 2D patterns of our samples at first sight look similar to those described by Neto and Davidson, but the second-order band is not visible. In our case, we do not have a nematic pseudo-lamellar ordering and, therefore, no second-order peak is observed.…”
Section: Resultssupporting
confidence: 87%
“…It was experimentally shown that the 2D patterns of all nematic phases contain two bands due to a pseudo-lamellar ordering of at least eight lamellar distances, and a third diffuse band, related to the micellar positional ordering in the direction perpendicular to the pseudo-lamellar ordering. The existence of a structural or “correlation” peak and its position at low q values as a typical for the nematic phase arrangement was also mentioned by Holmes et al, Pelletier et al, and Davidson et al The 2D patterns of our samples at first sight look similar to those described by Neto and Davidson, but the second-order band is not visible. In our case, we do not have a nematic pseudo-lamellar ordering and, therefore, no second-order peak is observed.…”
Section: Resultssupporting
confidence: 87%
“…A new peak arose at lower q ranges of 0.057 and 0.073 nm –1 for 2 and 5 wt % NCC, respectively. An anisotropic scattering pattern at a lower q range compared to that of the structure peak is indeed expected for nematic domains . This provides the structural proof for the formation of nematic domains within attractive NCC glasses.…”
Section: Resultsmentioning
confidence: 99%
“…Ribbon shaped particles can be modeled as parallelepipeds of dimensions length a , width b and thickness c ( a > b > c ), whose form factor is given by P r i b false( q false) = 0 normalπ / 2 0 π / 2 true[ sin q a sin θ cos φ 2 sin q b sin θ sin φ 2 sin q c cos θ 2 q a sin θ cos φ 2 q b sin θ sin φ 2 q c cos θ 2 true] 2 sin θ d θ d φ …”
Section: Methodsmentioning
confidence: 99%
“…In the limit of very small wave vectors and for a ≫ b , the intensity scattered by the ribbons follows the Zimm law, 1 I r i b ( q ) true( 1 + q 2 a 2 36 true) …”
Section: Methodsmentioning
confidence: 99%